Comparative study of the effects of custom-made insole and ordinary insole in adults with flexible flatfoot on different slopes - Jiang, Yangzheng; Yang, Jiantao; Tian, Hui; Jiang, Chuan; Wang, Hongzhu (Technology and health care, 2024)
BACKGROUND: Flatfoot (pes planus) is a common foot deformity, and its causes are mainly related to age, gender, weight, and genetics. Previous studies have shown that custom-made insoles could have a positive effect in improving plantar pressure and symptoms in individuals with flexible flatfeet, but it remains to be explored whether they can still show benefits in daily walking on different slopes. OBJECTIVE: This study aims to investigate a custom-made insole based on plantar pressure redistribution and to verify its effectiveness by gait analysis on different slopes. METHODS: We recruited 10 subjects and compared the peak pressure and impulse in each area between custom-made insole (CI) and ordinary insole (OI) groups. RESULTS: The results illustrate that CI raises the pressure in T area, improves the ability of the subjects to move forward in the slope walking, which was beneficial to gait stability. CONCLUSION: The redistribution of pressure in MF and MH area is promoted to provide active protection for subjects. Meanwhile, CI could decrease the impulse in MF area during uphill and level walking, which effectively reduces the accumulation of fatigue during gait. Moreover, avoiding downhill walking could be able to protect foot from injury in daily life.